1999
DOI: 10.1359/jbmr.1999.14.9.1583
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Biochemical Markers of Bone Turnover to Bone Density Changes in Postmenopausal Women: Results from the Postmenopausal Estrogen/Progestin Interventions (PEPI) Trial

Abstract: We assessed the associations of eight bone turnover markers (BTMs) with baseline and 1-year percentage changes in lumbar spine and hip bone mineral density (BMD) of 293 postmenopausal women undergoing treatment with hormone replacement therapy (HRT) or placebo using squared correlation coefficients (R 2 ). In 239 women assigned to treatment with estrogen alone or with with estrogen plus progestins (active treatment), mean percentage changes for all markers decreased significantly and remained below baseline va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1
5

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(56 citation statements)
references
References 17 publications
4
46
1
5
Order By: Relevance
“…A strong association may not be expected since TBBMC is primarily cortical bone and turnover markers are more indicative of cancellous bone activity. Although some investigators have shown no relationship between markers and bone mass [12], others have shown a small but significant correlation between a higher BMC with lower bone turnover [3,11,13], consistent with our data. Garnero et al [14] have also found a direct association between bone markers and fracture risk.…”
Section: Discussionsupporting
confidence: 91%
“…A strong association may not be expected since TBBMC is primarily cortical bone and turnover markers are more indicative of cancellous bone activity. Although some investigators have shown no relationship between markers and bone mass [12], others have shown a small but significant correlation between a higher BMC with lower bone turnover [3,11,13], consistent with our data. Garnero et al [14] have also found a direct association between bone markers and fracture risk.…”
Section: Discussionsupporting
confidence: 91%
“…The contribution (34.4%) of baseline clinical features in this study was higher than that in the PEPI trial [16], in which age, BMI and BMD together accounted for 13% of the percent change in spinal BMD. The majority of subjects of PEPI trial were Caucasians, which may be related to the difference of these contributions.…”
Section: Discussioncontrasting
confidence: 69%
“…(25,26) In the Women's Health Initiative (WHI) study of 16,608 women, at 5.2 years combination HT reduced hip and clinical vertebral fractures by 34% and all fractures by 24%. (27) Estrogen-only HT produced a similar reduction in fracture risk.…”
Section: Hormone Therapymentioning
confidence: 99%